Philosophy of School Punishment (Journal of Faculty of Education, 2021)
The relevance of punishment to the school situation is quite obvious. Discipline and general state of order have to be maintained if teaching is to proceed in a smooth manner. However, such conditions are not always guaranteed. The teacher then has to revert to punishment .The main objective of this paper is to highlight the meaning of "punishment" and ways in which it can possibly be justified, besides pinpointing the relevance of punishment to the educational process. For that purpose, philosophical and analytical method have been used in addition to reference to current literature on the subject. The conclusion that has been arrived at is that: if punishment is to be ataljustified, special considerations have to be paid to the issue concerning the aim or aims punishment is supposed to achieve. Punishment is normally justified in view of three broadly opposed approaches: the retributive, which is some sort of "hitting back", the utilitarian which is mostly associated with deterrence and the reformative which has special consideration for reform and rehabilitation. The retributivist approach is unacceptable in the educational environments while there is something to be said about determent and reformative theories. In the school situation, the absence of deterrence may cause, disorder on a large scale. The reformative approach is much more acceptable. Punishment can play a role in children`s moral and personal development when it is inflicted in appropriate situations on "offending" children on condition that they are shown the reason why it is inflicted upon them. However, Punishment, whatever form it may take, may be a necessary evil, or it is an evil nonetheless. It would, therefore, seem desirable punishment could be avoided as far as possible and only as a last resort, provided that the reasons and aims behind it are first examined and evaluated.
Keywords: Philosophy of School Punishment; educational process